Impactos de pequenas centrais hidrelétricas com diferentes arranjos na Bacia do Alto São Lourenço - Cruz, Rúbia Fantin da (2018)
The spread of Small Hydropower Plants (SHPs) around the world, based on the generation of energy from renewable sources, of low carbon and reduced environmental impacts, is part of the world scenario, considering that a large part of new and existing hydroelectric projects, including financed by global funds, fall into this category. However, their synergistic and cumulative environmental impacts are still poorly known and highly questioned, especially if their effects can extend to high biodiversity floodplains such as the Pantanal. In this context, flow measurements and sampling of water were performed upstream and downstream of rivers dammed by SHPs in the Upper Paraguay River basin plateau, headwaters of the Pantanal, in the São Lourenço River basin, and searches of documents available for public consultation were carried out in the environmental body. In the Upper São Lourenço basin, a set of SHPs of Medium height of fall of the projec was selected in the Tenente Amaral River sub-basin, which were grouped together as a complex, and the São Lourenço SHP of Low height of fall of the project, in the channel of the river of the same name, aiming to compare the effects of these different arrangements, within the category of SHP, on water quality. Fall of the project is understood as the vertical distance between the upper part of the water layer of the reservoir and that of the restitution channel downstream. For flow measurement, the reel method was used, and for the collection and analysis of water quality variables, the recognized standards were adopted. The comparison between upstream and downstream of the hydropower plants was done using the weighted average by the flow, due to the existence of several reservoir-forming rivers, or reservoirs in different rivers, as in the case of the SHPs of Medium height of fall existing in the Tenente Amaral River sub-basin, followed by non-parametric Kruskall-Walis test. The results indicated that the São Lourenço SHP, of Low height of fall, changed the dynamics of COD, total iron, suspended solids and turbidity, pH and dissolved oxygen, and that SHPs of Medium height of fall did not detectably influence water quality. The results also indicated a better cost-benefit ratio of SHPs with diversion channel in small tributaries compared to SHP with typical reservoir in the main channel in the Upper São Lourenço basin. And if all environmental studies for the implementation of new SHPs were carried out, the sub-basins of the Ibó, Prata and Beleza streams will be the most affected, occupying 15-20% of the main channels with reservoirs and diverted by diversion channels. The sub-basins of Tenente Amaral, Saia Branca and São Lourenço presented a small increase, with similar percentages to the current ones (10.1%, 20.6%, 3.9%, respectively).